Piperacillin-Induced Immune Hemolytic Anemia in an Adult with Cystic Fibrosis - Mahesh Bandara; David B. Seder; George Garratty; Regina M. Leger; Jonathan B. Zuckerman (Case Reports in Medicine)
We report a case of drug-induced immune hemolytic anemia (DIIHA) in an adult female with cystic fibrosis (CF), complicating routine treatment of a pulmonary exacerbation with intravenous piperacillin-tazobactam. Workup revealed a positive direct antiglobulin test (DAT) due to red blood cell (RBC)-bound IgG and C3 and piperacillin antibodies detectable in the patient's serum. The potential influence of CF transmembrane conductance regulator mutations on the severity of DIIHA is discussed. This report illustrates the importance of early identification of DIIHA, a rare complication of a commonly utilized medication in CF.